Impact Assessment of Sports Medicine Studies on Knowledge Production and Development - Fatemeh Zare; Fatemeh Makkizadeh; Afsaneh Hazeri (Pamukkale University, 2022)
In order to justify the investments made in research in the field of sports medicine, the outcomes and impacts of these investments should be assessed. The purpose of this study was to investigate the status and impact of sports medicine studies on the production and development of knowledge. In this descriptive study bibliometric and scientometric methods were used on 1145 scientific productions of sports medicine indexed in the Web of Science database. Data were analyzed through Excel Software, and cooperation maps were drawn using VOSviewer Software. According to the findings, the ratio of citations to the articles on the scientific productions of sports medicine was 23.17, which is higher than the clinical medicine area (6.8). The ratio of citations to the authors was 5.46% and 52 articles (4.54%) of the articles appeared without citations. The average impact factor of journals publishing papers was 3.9. Most of the articles were published with the collaboration of five authors. The results of the present study, based on a selected model and a combination of indicators of the UK's and Canadian Capital Return frameworks (from the production and development dimension), generally highlighted the validity and effectiveness of all indicators, including activity, quality, and development. The results revealed the most significant impact of the number and quality of each of the indicators in sports medicine in this area.